The Web as Corpus : theory and practice - Gatto, Maristella. (Corpus and Discourse, 2014)
"Is the internet a suitable linguistic corpus? How can we use it in corpus techniques? What are the special properties that we need to be aware of? This book answers those questions. The Web is an exponentially increasing source of language and corpus linguistics data. From user-generated Web 2.0 content to gigantic static information resources, the breadth and depth of information available is breathtaking - and bewildering. This book explores the theory and practice of "web as corpus". It looks at the most common tools and methods used and features a plethora of examples based on the author's own teaching experience. This book also bridges the gap between studies in computational linguistics, which emphasize technical aspects, and studies in corpus linguistics, which focus on the implications for language theory and use"--